Penerapan Analisis Jalur Terhadap Faktor-Faktor Yang Mempengaruhi Keberhasilan UMKM Binaan Rumah BUMN - Erwin, Erwin; S, Intan Maria Maharani (TIN: Terapan Informatika Nusantara, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy, contributing significantly to Gross Domestic Product (GDP) and employment. However, many MSME players face obstacles in optimizing their potential, especially in terms of capital, use of technology and halal permits. This research aims to analyze the influence of these factors on the production and income of MSMEs assisted by Rumah BUMN Medan City. This research dataset involved 100 MSMEs taken using the Stratified Simple Random Sampling technique. The research method used is descriptive quantitative with a correlational approach and path analysis (Path Analysis), to measure the direct and indirect influence of variables such as capital, length of business, halal permits, and production volume on income. The research results show that capital does not have a significant effect on the amount of production and income, while the length of business has a positive effect on these two variables. Halal permits have been proven to increase production but do not directly affect income. The production quantity variable functions as a strong mediator between exogenous factors and MSME income. The implication of this research is that MSME players need to focus on sustainable business management, increasing entrepreneurial experience, and obtaining halal certification to increase product competitiveness. In addition, the results of this research provide policy recommendations for the government to support the empowerment of MSMEs through more equitable and technology-based financing and training.